Soluciones barriales participativas, caso de estudio: barrio “Héroes del Cenepa” parroquia Punzara, cantón y provincia de Loja, período 2023 - Zambora Cueva, Cristhian Javier (2024)
The research is focused on contributing to the Heroes del Cenepa neighborhood in the Loja canton in the development of effective neighborhood solutions, through the application of participatory, independent and democratic processes oriented to meet citizen demands and local realities; collaborating with the neighborhood organization in the diagnosis of its main problems, providing training on mechanisms of citizen participation to empower neighborhood leadership and assisting in the generation of spaces for neighborhood residents to participate before local institutional authorities aimed at mitigating citizen demands. In addition, to achieve the objectives, a methodology based on action research was used, as well as techniques and tools for the collection of information, including training workshops, organization charts, observation sheets, surveys, interviews with key actors in the neighborhood, weighting and validation matrices of the central problem, problem and objective trees and the neighborhood action plan, which allowed the identification of three problems that need to be solved: The lack of a physical market for different businesses open to the public; the low level of police control and surveillance; and the lack of carriage bridges in sectors 1 and 2, which were validated in conjunction with the neighborhood residents. Finally, an action plan was prepared that can be implemented in the future by the competent neighborhood and institutional authorities, which includes possible solutions to the problems identified, as well as a timetable with pre-established deadlines for the fulfillment of the proposed activities.